Comparison of ethyl acetat fracination of ganitrie (Elaeocarpus sphearicus) seeds as anti bacterial of Staphylococcus aureus and determination of total flavonoid content - Sari, Yunita Kurnia; Suharsanti, Ririn; Wulandari, Wulandari (Journal of Health Management and Pharmacy Exploration, 2024)
Infectious disease is a disease coused by the presence pf pathogenic microbes. Stahpylococcus aureus is a gram positive aerobic bacterium that couses phyogenic infections on humans. Antibiotics are the best choise to treat an infections. The purpose of this study was to determine the antibacterial activity of ganitri seed (Elaeocarpus sphearicus) to determine the exstract ratio, the ethyl acetat fractination of ganitri seeds woth a concetration of 35% on the growth of staphylococcus aureus bacteria and to determine the total flavonoid content. Exctraction was carried out by maceration method for 3x24 hours with 96% ethanol as solvent. Exctraction fractination using 2 methods, the first method is using 30% ethanol, cloroform, and ethyl acetat as solvent. The second fractination method uses hot destiled water and ethyl acetat as solvents. The test result of total flavonoid content in ganitri (Elaeocarpus sphearicus) seeds in ethanol exstract were 38.009 mgEQ / g, fraction 1 of 99.512 mgEQ / g, fraction 2 of 68.235 mgEQ / g. From the result of the determinatoin of the ethyl acrtat fraction 1 had highest yield with an average value of 99,512 mgEQ/g. The antibacterial activity test was 35% in each sample ang using a positive control of ciprofloxcacin and a negative control of DMSO. Based on the result of the clear zone of the ethanol extract was 1.118 cm, the ethyl acetate 1 fraction was 1.170 cm, and the ethyl acetat 2 fraction was 0,956 cm.